2008
DOI: 10.1007/s00436-008-0982-8
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution and impact of cattle-raising on ticks in the Pantanal region of Brazil by using the CO2 tick trap

Abstract: This study evaluates the impact of cattle-raising on ticks associated with wildlife in the Pantanal region of Brazil, by trapping free-living ticks using a CO(2) tick trap. The traps were equally distributed in two areas: a 600-ha protected area (PA) and the Nhumirim Ranch (NR). Both areas are contiguous and located at the sub-region of Nhecolândia (18 degrees 59'S; 56 degrees 39'W), Pantanal, Brazil. In each area, four habitat types were selected: cerrado (tropical savanna), forest patches, lakes and soda lak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
0
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 29 publications
3
38
0
4
Order By: Relevance
“…The absence of A. rotundatum during flannel dragging supports the findings of Szabó et al (2007) and Cançado et al (2008) who also collected A. rotundatum from toads but not from dragging in different ecological regions. Based on these results and the finding of two engorged nymphs in the same habitat as the hosts, which seek refuges to avoid dehydration during the day, we assume that A. rotundatum exhibits nidicolous behavior at the studied site.…”
Section: Discussionsupporting
confidence: 84%
“…The absence of A. rotundatum during flannel dragging supports the findings of Szabó et al (2007) and Cançado et al (2008) who also collected A. rotundatum from toads but not from dragging in different ecological regions. Based on these results and the finding of two engorged nymphs in the same habitat as the hosts, which seek refuges to avoid dehydration during the day, we assume that A. rotundatum exhibits nidicolous behavior at the studied site.…”
Section: Discussionsupporting
confidence: 84%
“…One negative aspect of CO 2 traps is their cost and the need for transportation of heavy dry ice before it sublimes away. Alternatively, traps that use other CO 2 sources such as the reaction between calcium carbonate and lactic acid (BUTLER et al, 1984;CANÇADO et al, 2008) may be used. It seems that these two kinds of CO 2 traps have similar results (GUEDES et al, 2012), but although the alternative CO 2 source is cheaper, it still has costs, in that a lot of material has to be carried and setting up each trap is time-consuming.…”
Section: Discussionmentioning
confidence: 99%
“…In visual searches, a trained observer looks for questing ticks on the tips of the leaves along animal trails (TERASSINI et al, 2010). Carbon dioxide traps are systems using a CO 2 source over a white surface that are placed on the ground to attract hunter ticks (OLIVEIRA et al, 2000;CANÇADO et al, 2008). Because dragging is convenient and inexpensive, it is the most commonly used method for estimating the abundance of free-living ticks (TACK et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This would also explain the tendency for a greater abundance of A. cajennense in the more disturbed area (Jequitibá Rosa trail). This species is commonly found in high abundance in impacted areas under high anthropogenic pressure (ARZUA, 2007;CANÇADO et al, 2008;SILVEIRA;FONSECA, 2011). Previous studies have reported that the prevalence of A. cajennense in tropical forests is low, although it is well adapted to a variety of environments (ESTRADA-PEÑA et al, 2004;SZABÓ et al, 2007;VERONEZ et al, 2010).…”
Section: Palavras-chave: Amblyomma Brasiliense Amblyomma Cajennensementioning
confidence: 99%